Clinical Decision Support System for Treatment and Management strategies of COPD - Anakal, Sudhir; P, Sandhya (International Journal of Computer Sciences and Engineering, 2022)
n this advanced technology most of the modern hospitals are adopting Clinical Decision Support System (CDSS) model for the diagnosis and management of most of the medical related problems. The system plays a vital role in medical decisions. In the present study, we are developing a CDSS which helps the physician to take better medical decision on the diagnosis of Chronic Obstructive Pulmonary Disease (COPD). The system also helps to take appropriate decision on treatment and management strategies for patients who are suffering from COPD. COPD is an increased inflammatory immune response to the lungs to particles and gases, from cigarette smoke, neutrophils. COPD is considered as a long term dysfunction, disease but its natural history as it occurs at intervals by periods of acute deterioration or exacerbations. Patients with COPD can have a sign of relief and be positive in today’s generation because new medical therapies with alternate remedies. Any disease requires well-planned management strategies. In this paper we have designed a CDSS for treatment and management for COPD.